Case Report: Practice of whole-course pharmaceutical care: a case in hypertrophic cardiomyopathy and a review of the pharmacist’s role - Li, Liu-Cheng; Zhang, Su; Sun, Jia-Bin; Xu, Yao-Yao; Mao, Kai-Li (Frontiers in Cardiovascular Medicine, 2025)
Clinical pharmacists supported clinicians in medication planning and health education for a male patient diagnosed with hypertrophic cardiomyopathy (HCM). Therapeutically, diltiazem was replaced with metoprolol to further alleviate symptoms. Whole-blood exon sequencing revealed a pathogenic mutation in the beta-myosin heavy chain gene (MYH7, OMIM #160760), consistent with dominant inheritance. Furthermore, low-intensity exercise and screening of the patient’s children were recommended. In addition, we provided an overview of current therapeutic approaches, emphasizing potential novel agents and non-pharmaceutical interventions for HCM management. This is the first case report to highlight not only updates in HCM treatment but also the pharmacist’s role in long-term HCM management.